2007
DOI: 10.1097/01.tp.0000264189.58324.91
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Renal Transplant Function in Recipient of Simultaneous Kidney and Pancreas Transplant Maintained With Two Prednisone-Free Maintenance Immunosuppressive Combinations: Tacrolimus/Mycophenolate Mofetil Versus Tacrolimus/Sirolimus

Abstract: Our data suggest that, in SPK recipients, long-term kidney allograft survival and function are not statistically different. A trend toward an increased rate of renal allograft loss was found in the Tac/SRL-treated group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…Whether sirolimus-based immunosuppression affects outcome after SPK is unknown. Another research group recently showed [28] a trend towards increased prevalence of renal allograft loss in a tacrolimus/sirolimus-treated group. We found a statistically significant higher number of patients with pancreas-related complications in the group treated with the tacrolimus/sirolimus regimen.…”
Section: Discussionmentioning
confidence: 97%
“…Whether sirolimus-based immunosuppression affects outcome after SPK is unknown. Another research group recently showed [28] a trend towards increased prevalence of renal allograft loss in a tacrolimus/sirolimus-treated group. We found a statistically significant higher number of patients with pancreas-related complications in the group treated with the tacrolimus/sirolimus regimen.…”
Section: Discussionmentioning
confidence: 97%
“…RDP has been used with a number of different maintenance protocols (27)(28)(29)(30). A recent meta-analysis by Pascual et al (12) suggested that RDP with cyclosporine, but not tacrolimusbased protocols, was associated with increased AR rates, whereas RDP with tacrolimus, but not cyclosporine-based protocols, was associated with increased NODM.…”
Section: Discussionmentioning
confidence: 99%
“…Mint minden szerv átül-tetésénél, a hasnyálmirigy-transzplantációnál is négy gyógyszercsoportból (kalcineurininhibitorok, antimetabolitok, szteroid és mTOR-inhibitorok) tetszőlegesen összeállított kombinációt választhatunk. A legtöbb hasnyálmirigy-transzplantációs program két kombináció valamelyikét választja [33]. Világszerte leggyakrabban a szteroid, tacrolimus, mycophenolat-mophetil kombinációt használják.…”
Section: Immunszuppresszióunclassified